ASPECTS UNDERLYING THE MODIFICATION OF BRIDAL COSTUME IN GORONTALO AT THE WEDDING RECEPTION - Hariana Hariana; G.R. Lono Lastoro Simatupang; Timbul Haryono; SP. Gustami (Universitas Gadjah Mada, 2017)
The visualization of the Gorontalonese bridal costume worn at the wedding reception is increasingly diverse in terms of the modification forms. The modification can be seen in the design elements including shape, texture, color, material, and accessory. Furthermore, the modification of the current costume makes the functional value of the bridal costume different from the already patterned one, which can be seen from its social, symbolic, and economic values of the Gorontalo community. The data in this study was collected through the review of books and previous studies related to the wedding clothing, the interviews, and the observation of bridal costumes and analyzed using the qualitative data analysis approach. The observation of unmodified bridal costume objects was done at the Dulahopa Traditional House in Gorontalo, while that of modified bridal costume objects was conducted on the widely used bridal costumes within the last two years in Gorontalo. The purpose of this study was to find out the aspects underlying the modification of bridal costume in Gorontalo. The results show that Gorontalo people tend to choose modified wedding dresses in the wedding party. Moreover, this study suggests that the bridal costume modification is influenced by the family’s social status in Gorontalonese community, migratory Gorontalonese people (staying outside the area of origin), and technological advancement.